Strategi Komunikasi Persuasif Sekolah Alam Indonesia Palembang dalam Meningkatkan Kesadaran Lingkungan pada Siswa - Maharani, Ajeng Sapna; Walian, Anang (Fakultas Ushuluddin Adab dan Dakwah IAIN Lhokseumawe, 2025)
This study aims to analyze the persuasive communication strategies implemented by teachers at the Indonesian Nature School in Palembang to increase students' environmental awareness. The study used a descriptive qualitative approach through observation, in-depth interviews, and field documentation. The results showed that teachers implemented persuasive communication strategies based on Johnson Alvonco's five stages, namely informing, explaining, convincing, persuading, and gaining agreement. These strategies were realized through verbal communication, teacher role models, and active student involvement in environmental activities. The findings of this study indicate that systematic persuasive communication can shape sustainable changes in students' attitudes, behaviors, and ecological awareness, thus contributing to strengthening value-based environmental education and da'wah communication.